PEMUTUSAN KONTRAK KERJA AKIBAT PANDEMI COVID-19 DIHUBUNGKAN DENGAN PASAL 164 UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Wilda Oktavianingrum Sudibyo; Ateng Sudibyo (Journal Presumption of Law, 2022)
Everycitizen has the right to a decent job and livelihood for humanity, but the willingness of employment is so limited that not everyone gets the same luck in getting a job, especially in the field of formal work such as factory workers, office employees, people with professional work and others. With the Covid-19 pandemic in Indonesia, there are so many terminations carried out by employers, so that more and more citizens do not have jobs. This research uses a normative juridical approach andthe current research is descriptive analytical. Data collection is carried out through literature studies in order to obtain secondary data, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The technical analysis used in this study is a qualitative analysis technique. Based on the results of the study, it is known that termination of employment can be carried out if the company closes due to compelling circumstances caused by the spread of Covid-19, but fortermination of employment must be carried out inaccordancewith the provisions of Article 164 Undang-U ndang Number 13 of 2003 concerning K Employment, but if a company experiences difficulties that can have an effect on employment, then termination must be a last resort. Arbitrary layoffs of workers in any situation, including in the covid-19 pandemic situation, are basically not allowed and legal remedies that can be made in the settlement of industrial relations disputes include through bipartait settlements, mediation, conciliation, arbitration, and industrial relations courts.